In silico and In vitro Characterization of Potent CDK2 Inhibitors as Probable Cancer Therapeutics - Aloqbi, Akram Ahmed (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Cyclin-Dependent Kinases (CDKs) are a family of serine/threonine protein kinases that play pivotal roles in the regulation of the cell cycle and various cellular processes. Among them, CDK2 is a crucial regulator of the G1/S phase transition and is crucial for the proper progression of the cell cycle. Dysregulation of CDK2 activity is frequently observed in various types of cancer, making it an attractive therapeutic target. Dinaciclib, a potent CDK2 inhibitor, has demonstrated clinical efficacy in the treatment of several malignancies. However, the development of novel CDK2 inhibitors with superior pharmacological properties remains an active area of research to improve therapeutic outcomes and address the limitations associated with existing agents. Materials and Methods: A comprehensive screening process began with the retrieval of 292 compounds from the PubChem database. The Lipinski rule of five was applied to narrow down the pool to 233 compounds with favorable drug-like properties. The selected compounds were then evaluated and compared to Dinaciclib using molecular docking and Molecular Dynamics (MD) simulations. In vitro assays were conducted to validate the inhibitory effect of lead molecule. Results: The computational analysis revealed that CID-23569275 emerged as the most promising lead compound. This compound exhibited higher LibDock scores, indicating stronger binding affinity towards CDK2 compared to Dinaciclib. MD simulations further demonstrated that CID-23569275 maintained greater conformational stability, as evidenced by their lower Root Mean Square Deviation (RMSD) and Root Mean Square Fluctuation (RMSF) values. Moreover, the combined evidence from the enzyme inhibition assay and fluorescence emission spectra strongly supports the effectiveness of CID-23569275 in inhibiting CDK2 activity. Conclusion: This comprehensive computational study has successfully identified CID-23569275 as potent lead compound for CDK2 inhibition, exhibiting superior pharmacological properties compared to the reference compound, Dinaciclib. The enhanced binding affinity and conformational stability of this lead candidate warrant its continued investigation through rigorous in vitro and in vivo studies to validate their therapeutic potential in cancer therapy.
Keywords: CDK2; Dinaciclib; Molecular Docking; Molecular Dynamics; ADMET; PubChem and; Enzymatic assay